The Relationship among Economic Growth, Trade, Unemployment, and Inflation in South Asia: A Vector Autoregressive Model Approach - Nguyen, Anh Tru (Asian Journal of Economics and Empirical Research, 2018)
The article aims to investigate the causal relationship among economic growth, exports, imports, unemployment, and inflation in five developing countries in South Asia for the last two decades (1997-2016) using a VAR model. We found that GDP has a negative relationship with inflation, while imports positively affect inflation in South Asian countries. Results demonstrated that there are no directional causalities between GDP, exports, imports, and unemployment rate and other variables in the short run. In contrast, there is a directional causality between inflation rate and other variables in the short run. We also found that there is a long-term relationship among economic growth, exports, imports, unemployment, and inflation in South Asia. Lastly, policies are recommended in order to ensure economic growth and a sustainable development in the South Asia.